Eosinophilic cystitis, a rare cause of persistent haematuria in a diabetic dog - Braz, Larissa Ayane Do Nascimento [UNESP]; Cruz, Nathan da Rocha Neves [UNESP]; Santos, Gabriel Fernando Müller; Magalhães, Larissa Fernandes; Crivellenti, Leandro Zuccolloto (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
Eosinophilic cystitis is a rare inflammatory disorder characterized by eosinophilic infiltration of entire layers of the bladder wall. The condition has been described in adults, children, and dogs. However, there are no consensus guidelines for the treatment of eosinophilic cystitis. Although human and veterinary literature reviews show some effectiveness in management with corticosteroids, antihistamines, and antibiotics, a variety of serious and frequent side effects are associated with steroid therapy. As a result, steroids are relatively contraindicated for patients with diabetes mellitus and Cushing’s syndrome. A five-year-old neutered male chow-chow with controlled diabetes was referred with an 18-month history of malodorous urine, gross haematuria, and dysuria that were nonresponsive to antibiotics. The findings on general examination were unremarkable except for abdominal suprapubic discomfort. The complete blood count and biochemical profile (such as urea and creatinine) were normal except for mild peripheral eosinophilia. Although ultrasonography, bladder contrast radiography, and urine cytology findings indicated malignancy, with the presence of atypical urothelial cells, histopathology confirmed eosinophilic cystitis. Management with cyclosporine was adequate with complete remission of haematuria. This case report presents the first reported successful use of cyclosporine for the treatment of eosinophilic cystitis in a dog with diabetes.
Cistite eosinofílica, uma causa rara de hematúria persistente em um cão diabético
Keywords: Cyclosporine; Enterobacter; Eosinophilia; Klebsiella pneumoniae; Multiple drug-resistance